EFFECTIVENESS OF C1-C2 SUSTAINED NATURAL APOPHYSEAL GLIDE COMBINED WITH DRY NEEDLING ON PRESSURE POINT THRESHOLD AND HEADACHE DISABILITY IN CERVICOGENIC HEADACHE. - Patra, Ramesh Chandra; Mohanty, Patitapaban; Gautam, Ajay P (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The main objective of this study was to evaluate the effectiveness of dry needling and mulligan C1-C2 sustained natural apophyseal glides (SNAGs) in increasing pressure point threshold and reducing headache disability in patients with CGH. Methods: This study was conducted on 150 patients. They were divided into three groups for the purpose of the study. Group A was referred to as the dry needling group. They were subjected to dry needling for treating the pain. Group B was the manual therapy group. The patients in this group were subjected to C1-C2 SNAGs. Group C was the combined group. Patients belonging to this group were given C1-C2 SNAGs along with dry needling. Results: Statistical analysis paired t-test was used for comparison of the mean within every group where it showed significant improvement in all the parameter (p<0.05). Conclusion: There was a consistent reduction in tenderness and improvement in disability of the patients belonging to all groups. However, Group C, where the patients were subjected to combined treatment, showed better results. Results of this study indicate that dry needling along with mulligan C1-C2 SNAGs is more beneficial in patients suffering from cervicogenic headaches.